2021
DOI: 10.1371/journal.pone.0253190
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of sweet corn hybrids in response to crowding stress

Abstract: Crop tolerance to crowding stress, specifically plant population density, is an important target to improve productivity in processing sweet corn. Due to limited knowledge of biological mechanisms involved in crowding stress in sweet corn, a study was conducted to 1) investigate phenotypic and transcriptional response of sweet corn hybrids under different plant densties, 2) compare the crowding stress response mechanisms between hybrids and 3) identify candidate biological mechanisms involved in crowding stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…As mentioned, hybrids differ in density tolerance, even among modern lines that are commercially available and grown (Williams 2012(Williams , 2015. The physiological underpinnings of density tolerance variations in sweet corn have received limited study (Choe et al 2016(Choe et al , 2021Revilla et al 2021). Even within a hybrid, EOPD and YOPD can vary widely across environments (Dhaliwal and Williams 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, hybrids differ in density tolerance, even among modern lines that are commercially available and grown (Williams 2012(Williams , 2015. The physiological underpinnings of density tolerance variations in sweet corn have received limited study (Choe et al 2016(Choe et al , 2021Revilla et al 2021). Even within a hybrid, EOPD and YOPD can vary widely across environments (Dhaliwal and Williams 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent on-farm research throughout the Midwest shows hybrids with superior PDT are being underplanted (Dhaliwal and Williams 2019, 2020b). Moreover, transcriptional and functional analyses have identified candidate physiological processes involved in sweet corn PDT (Choe et al 2016, 2021). While PDT is intraspecific competition (crop vs. crop), not interspecific competition (crop vs. weed), previous research has shown the two are linked (Williams and Boydston 2013).…”
Section: Present—ars Weed Science Researchmentioning
confidence: 99%